Ocorrência de pontes de miocárdio em bovinos das raças Gir, Guzerá, Indubrasil e Nelore (Veterinária Notícias, 2014)
Ocorrência de pontes de miocárdio em bovinos das raças Gir, Guzerá, Indubrasil e Nelore